2006
DOI: 10.22146/gamaijb.5614
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Overall Satisfaction in Service Customer Relationships

Abstract: Garbarino and Johnson (1999) find that there is no correlation between overall satisfaction and loyalty in the field of customer relationship. Their finding indicates that satisfaction is no longer an important issue in managing service organizations. This research investigates the existence of satisfaction in service organizations, which have relationships with customers. Contrary to Garbarino and Johnson’s (1999) finding, this research finds that overall satisfaction, through commitment, has a relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
0
15
0
3
Order By: Relevance
“…Therefore, it needs to implement an effective business strategy to be able to manage its relationships with students. Customer satisfaction is still a main issue with respect to managing service organizations, especially service organizations that have customer-relationship strategy (Zulganef, 2006). The results of the SERVQUAL gap analysis provide very useful information to institutions concerning the desires of its students.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it needs to implement an effective business strategy to be able to manage its relationships with students. Customer satisfaction is still a main issue with respect to managing service organizations, especially service organizations that have customer-relationship strategy (Zulganef, 2006). The results of the SERVQUAL gap analysis provide very useful information to institutions concerning the desires of its students.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore satisfaction will remain a primary objective. Morgan and Hunt (1994) and Zulganef (2006) further revealed a significant relationship between satisfaction with commitment.…”
Section: Commitment Loyaltymentioning
confidence: 85%
“…All three of these studies illustrate that consumer satisfaction is a predictor for commitment. Zulganef (2006) revealed that the relationship between overall satisfaction with the commitment can be developed based on the concept of loyalty stages proposed by Dharmmesta (1999), research Morgan and Hunt (1994), and the principle of means-end chain proposed by Peter and Olson (1999 ). Dharmmesta (1999) revealed the four-stage loyalty.…”
Section: Commitment Loyaltymentioning
confidence: 99%
“…Buna göre, sadık müşteri kavramının daha iyi anlaşılabilmesi ve incelenebilmesi için tatmin ile birlikte farklı faktörlerin de araştırma kapsamına alınması gerektiği görülmektedir (Chitturi vd., 2008). Bu doğrultuda Zulganef (2006), tatminin, güven ve bağlılık aracılığıyla satın alma niyetini ve sadakati etkilediğini ortaya koymaktadır. Netice olarak özellikle ilişkisel pazarlama çerçevesinde tüketici pazarlarına yönelik yapılmış olan güncel çalışmalar; tatminin doğrudan olmasa da güven ve bağlılık aracılığıyla tüketici davranışı üzerinde etkili olduğunu ortaya koymaktadır.…”
Section: Marka Tatmini Ve Marka Sadakati İlişkisiunclassified